1973
DOI: 10.1021/ic50121a049
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency infrared spectra of complexes which exhibit magnetic crossover. I. Iron(II) complexes of 1,10-phenanthroline and 2,2'-bipyridine

Abstract: Registry No. BrMn(CO)s, 14516-54-2; ClMn(CO)s, 14100-30-2; IMn(CO)s, 14879-42-6; ds-BrMn(CO)4-(CNCH3), 37474-14-9. Acknowledgments. The authors wish to acknowledge Dr. P. M. Treichel and his research group for supplying samples of the pentacarbonylmanganese halides. We are especially grateful to Dr. G. E. Dirreen for supplying the sample of Mn(CO)4(CNCH3)Br. We are grateful to Dr. A. F. Orchard for informing us of the presence of the 9a2 band and useful discussions. This work was supported by the National S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(41 citation statements)
references
References 1 publication
(1 reference statement)
4
37
0
Order By: Relevance
“…The tentative explanation is that the whole sample was not equilibrated at the present temperature.) As discussed earlier, 3,34 in the FIR region 100-500 cm 1 significant shifts of the ligand-central Fe(II) stretching vibrations are expected. One reason is that, upon transition to the HS state (in an ideal octahedral environment), an electron is promoted from a bonding t 2g orbital into an antibonding e g orbital thus weakening the metal-to-ligand binding.…”
Section: Ir and Raman Spectrasupporting
confidence: 57%
See 1 more Smart Citation
“…The tentative explanation is that the whole sample was not equilibrated at the present temperature.) As discussed earlier, 3,34 in the FIR region 100-500 cm 1 significant shifts of the ligand-central Fe(II) stretching vibrations are expected. One reason is that, upon transition to the HS state (in an ideal octahedral environment), an electron is promoted from a bonding t 2g orbital into an antibonding e g orbital thus weakening the metal-to-ligand binding.…”
Section: Ir and Raman Spectrasupporting
confidence: 57%
“…In previous work, 3,34,37,38 iron-ligand bond stretching vibrations could be identified by means of isotope substitution. Accordingly, they should be found in the range 400-500 cm 1 for the LS isomer and in the wavenumber range 250-300 cm 1 for the HS isomer.…”
Section: Assignment Of Vibrational Bandsmentioning
confidence: 99%
“…This corresponds to an increase of the force constant by a factor of two. Comparison of the assignment made by Takemoto et al [44] with the calculated normal coordinates suggests that one Fe-N-CS bending mode has been assigned as Fe-N bond-stretching mode by Takemoto, leading thus to an increase of the Fe-N bond-stretching frequency shift.…”
Section: Vibrational Modes and Ir Raman And Nis Spectramentioning
confidence: 87%
“…It is very difficult to make a complete assignment of vibrational modes to the large number of observed lines. For the well-studied SCO complexes [Fe(phen) 2 (NCS) 2 ] (phen=1,10-phenanthroline) Takemoto et al [44] reported a decrease of the iron-ligand bond stretching frequency by a factor of two. Similar frequency shifts have been reported for several other SCO complexes [45].…”
Section: Vibrational Modes and Ir Raman And Nis Spectramentioning
confidence: 99%
“…The first detailed study aimed at assigning metal-ligand vibrational modes in SCO compounds was carried out by Takamoto and Hutchinson [14][15][16][17] using metal isotope substitution on [Fe(phen) 2 (NCS) 2 ] and related compounds. They assigned a shift of Fe-N(phen) and Fe-N(NCS) stretching frequencies from 220 cm 1 (HS) to 375 cm 1 (LS) and from 252 cm 1 (HS) to 530 cm 1 (LS), respectively.…”
Section: Metal-ligand Vibrationsmentioning
confidence: 99%